The impact of non‐invasive prenatal testing on anxiety in women considered at high or low risk for aneuploidy after combined first trimester screening. (14th August 2017) - Richmond, Zara; Fleischer, Ron; Chopra, Maya; Pinner, Jason; D'Souza, Mario; Fridgant, Yelena; Hyett, Jonathan
Abstract : What's already known about this topic? High‐risk combined first trimester screening results may create high levels of state anxiety. This anxiety usually resolves upon receipt of a normal karyotype result through invasive testing. However, invasive testing itself provokes anxiety. What does this study add? Both high‐risk and low‐risk combined first trimester screening populations demonstrated similar trait anxiety levels and experienced a statistically significant reduction in state anxiety to similar final levels after they received a low‐risk non‐invasive prenatal testing result. Abstract: Objective: The aim of this study was to (1) examine the psychological impact of non‐invasive prenatal testing (NIPT) in women with a high‐risk (≥1 : 300) and low‐risk (≤1 : 301) result on combined first trimester screening (cFTS) and (2) to examine factors influencing anxiety and decision‐making in both risk populations. Method: Questionnaires and structured interviews were administered to low ( n = 50) and high ( n = 63) risk women at the time of NIPT blood draw (point A) and again at least 1 week after receiving their NIPT result (point B). Anxiety levels were measured at these two time points using the State–Trait Anxiety Inventory. Results: Both high‐risk and low‐risk cFTS groups demonstrated similar intrinsic (trait) anxiety levels (36 ± 10 vs 35 ± 10; p = 0.70). High‐risk women had significantly higher levels of state anxiety at point A than low‐risk women (42 ± 11 vs 36 ± 11; p < 0.01). Both groups had a statistically significant reduction ( p < 0.01), to similar final levels of state anxiety at point B (30 ± 11 vs 29 ± 8; p = 0.61). Conclusion: Women receiving a high‐risk result on cFTS have higher levels of state anxiety than their low‐risk counterparts. Following a low‐risk NIPT result, the anxiety levels in both populations are reduced to similar levels. © 2017 John Wiley & Sons, Ltd.